The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0734242x15594248
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare waste management research: A structured analysis and review (2005–2014)

Abstract: The importance of healthcare waste management in preserving the environment and protecting the public cannot be denied. Past research has dealt with various issues in healthcare waste management and disposal, which spreads over various journals, pipeline research disciplines and research communities. Hence, this article analyses this scattered knowledge in a systematic manner, considering the period between January 2005 and July 2014. The purpose of this study is to: (i) identify the trends in healthcare waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 97 publications
0
48
0
3
Order By: Relevance
“…Some studies have identified the importance of training programs directed to health workers, HCW management teams and waste handling workers in order to improve the global approach on HCWM [47, 48]. However, this has been neglected in Brazil [23] and may be one of the reasons behind the difficulties on HCWM faced by this country.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified the importance of training programs directed to health workers, HCW management teams and waste handling workers in order to improve the global approach on HCWM [47, 48]. However, this has been neglected in Brazil [23] and may be one of the reasons behind the difficulties on HCWM faced by this country.…”
Section: Discussionmentioning
confidence: 99%
“…Legal provisions and definitions are also different, thus adding to uncertainties and making comparisons difficult [37][38][39].…”
Section: Dialysis In the Global Contextmentioning
confidence: 99%
“…(2,3, 4) Torna-se pertinente integrar o plano de formação específico na área de gestão de Resíduos Hospitalares (RH) no plano de formação institucional (5). As formações nesta área devem atender ao levantamento das necessidades de formação diagnosticadas, devendo ser adequadas ao conteúdo funcional dos diferentes grupos profissionais (6,7). Para um estudo neste contexto selecionou-se o CHSJ (Centro Hospitalar de S.João) tendo por base a sua dimensão e diferenciação da prática clinica.…”
Section: Introductionunclassified
“…(2,3,4) It is appropriate to integrate the specific training plan in the area of Hospital Waste Management into the institutional training plan (5). Training in this area should take into account the determined training needs and should be adequate to the functional content of the different professional groups (6,7). For a study in this context, the HCSJ (Hospital Center of S. João) was selected based on its size and differentiation of the clinical practice.…”
Section: Introductionmentioning
confidence: 99%